Utilizing Postcolonial Theory in Christian Education - Elraphoma, Erich von Marthin (Theologia in Loco, 2021)
A postcolonial study is an approach to analyzing a social issue or problem. One of the terms often used in this study is the Subaltern Theory. This terminology refers to marginalized people’s groups by a hegemonic power in the social system for specific reasons, such as social class, religion, gender, race, language, and culture. The complexity of colonialization effects makes us unaware if perspective, philosophy, and knowledge are strongly influenced by colonialism, so that regulations, policies, politics, and even our education system oppress others, the subaltern. Therefore, this essay utilizes a postcolonial study (specifically subaltern theory) that shows who and how groups of people are marginalized in society’s system. Subaltern theory becomes a system of thinking to decolonize all dimensions of life, including religious education. Moreover, this paper uses a case marginalization in a religious education system or curriculum in Britain, as Liam Gearon wrote. Gearon examines the legal basis, system, and curriculum of religious education in Britain. Gearon’s arguments and subaltern theory show the reasons for the needs and encourage Christian Education to awaken awareness and critical thinking, then move to change circumstances. The subaltern theory helps religious education examine its curriculum and content not to perpetuate oppression but rather to develop critical thinking that can produce deep reflection and free creativity to overcome social and theological issues.